Criteria of the German Consortium for Hereditary Breast and Ovarian Cancer for the Classification of Germline Sequence Variants in Risk Genes for Hereditary Breast and Ovarian Cancer - Wappenschmidt, Barbara; Hauke, Jan; Faust, Ulrike; Niederacher, Dieter; Wiesmüller, Lisa; Schmidt, Gunnar; Groß, Evi; Gehrig, Andrea; Sutter, Christian; Ramser, Juliane; Rump, Andreas; Arnold, Norbert; Meindl, Alfons (Geburtshilfe und Frauenheilkunde, 2020)
More than ten years ago, the German Consortium for Hereditary Breast and Ovarian Cancer (GC-HBOC) set up a panel of experts (VUS Task Force) which was tasked with reviewing the classifications of genetic variants reported by individual centres of the GC-HBOC to the central database in Leipzig and reclassifying them, where necessary, based on the most recent data. When it evaluates variants, the VUS Task Force must arrive at a consensus. The resulting classifications are recorded in a central database where they serve as a basis for ensuring the consistent evaluation of previously known and newly identified variants in the different centres of the GC-HBOC. The standardised VUS evaluation by the VUS Task Force is a key element of the recall system which has also been set up by the GC-HBOC. The system will be used to pass on information to families monitored and managed by GC-HBOC centres in the event that previously classified variants are reclassified based on new information. The evaluation algorithm of the VUS Task Force was compiled using internationally established assessment methods (IARC, ACMG, ENIGMA) and is presented here together with the underlying evaluation criteria used to arrive at the classification decision using a flow chart. In addition, the characteristics and special features of specific individual risk genes associated with breast and/or ovarian cancer are discussed in separate subsections. The URLs of relevant databases have also been included together with extensive literature references to provide additional information and cover the scope and dynamism of the current state of knowledge on the evaluation of genetic variants. In future, if criteria are updated based on new information, the update will be published on the website of the GC-HBOC (https://www.konsortium-familiaerer-brustkrebs.de/).Das Deutsche Konsortium für Familiären Brust- und Eierstockkrebs (GC-HBOC) etablierte vor über 10 Jahren eine Expertengruppe (VUS Task Force), um die von den einzelnen Zentren des GC-HBOC an die zentrale Datenbank in Leipzig gemeldeten Varianten hinsichtlich ihrer Klassifizierung zu überprüfen und ggf. nach aktueller Datenlage neu einzustufen. Die innerhalb der VUS-Task Force konsentierten Variantenbewertungen und resultierenden -klassifizierungen werden in einer zentralen Datenbank hinterlegt und sind als Grundlage zu berücksichtigen, um eine einheitliche Bewertung bereits bekannter wie auch neu identifizierter Varianten innerhalb der verschiedenen Zentren des GC-HBOC zu gewährleisten. Die standardisierte VUS-Bewertung durch die VUS Task Force ist ein zentrales Element des vom GC-HBOC ebenfalls etablierten Recall-Systems. Dieses dient der Weitergabe der Informationen an die in den Zentren betreuten Familien im Falle einer aufgrund neuer Erkenntnisse aktualisierten Neubewertung von bereits klassifizierten Varianten. Die in Anlehnung an international etablierte Bewertungsverfahren (IARC, ACMG, ENIGMA) angepassten Bewertungsalgorithmen der VUS Task Force werden in diesem Artikel anhand der zugrundeliegenden Entscheidungskriterien präsentiert, die gemäß eines priorisierenden Fließschemas zum Klassifizierungsergebnis führen. Weiterhin werden genspezifische Regelungen und Besonderheiten, die für einzelne mit Brust- und/oder Eierstockkrebs assoziierte Risikogene zu berücksichtigen sind, in einzelnen Unterkapiteln dargelegt. Um dem Umfang und der Dynamik des aktuellen Wissens zur Variantenbewertung gerecht zu werden, sind neben umfangreichen Literaturverweisen insbesondere auch die URLs von relevanten Datenbanken angegeben. In Zukunft sollen an neue Erkenntnisse angepasste Kriterien auf der Webseite von GC-HBOC (https://www.konsortium-familiaerer-brustkrebs.de/) veröffentlicht werden.
Keywords: hereditary breast/ovarian cancer; classification of genetic variants; risk genes